Molecular Characterization of Begomovirus on Cucumber in Java - Listihani Listihani; Tri Asmira Damayanti; Sri Hendrastuti Hidayat; Suryo Wiyono (Jurnal Perlindungan Tanaman Indonesia, 2019)
A survey on several cucumber cultivation areas in West Java, Central Java, Yogyakarta, and East Java found many plants showing typical Begomovirus symptoms such as yellow mosaic, cupping, and vein banding. This study was aimed to determine disease frequency, detection and molecular characterization of the causal virus of those symptoms on cucumber in Java. Sampling was conducted by purposive sampling by collecting 50 symptomatic plants from each location in West Java (Indramayu, Subang, and Bogor), Central Java (Brebes and Klaten), Yogyakarta (Kulon Progo), and East Java (Nganjuk, Kediri, and Tulungagung). The detection and disease frequency was determined based on DIBA test using a specific antiserum of Tomato leaf curl New Delhi virus (ToLCNDV) and Squash leaf curl virus (SLCV). The identification of nucleic acid was conducted by PCR using specific primer of ToLCNDV and SLCV, DNA cloning, and sequencing. The results of serological detection showed the disease frequency of ToLCNDV and SLCV ranged from 92.77-100% and 78.33-93.3%, respectively. PCR using specific primer of ToLCNDV successfully amplified the coat protein gene at a size of 600 bp from all samples. Homology nucleotide and amino acid sequences among ToLCNDV Java isolate ranging from 95.6-99.2% and 99.7-100%. ToLCNDV isolates Java had highest nucleotide and amino acid sequences similarity with cucumber isolate from Klaten, Indonesia (AB613825) ranging from 96.1-98.1% and 99.7-100%, and was considered as “Indonesia” strain. SLCV not amplified on all samples by PCR using specific primer, indicating it might not present yet on cucumber in Java.